The Utilization of Assembler Edu (AR) as a Learning Media to Increase Students' Learning Interest in Komjardas Class X Computer and Network Engineering Vocational School Unitomo Surabaya - AbdiKusumo, Wisnu Candi; Sucipto, Sucipto; Tobing, Victor Maruli Tua L. (Journal of Educational Sciences, 2026)
The research is motivated by the challenges in Basic Computer and Network learning (Komjardas) that require concrete visualization of network devices, while conventional media such as textbooks are considered less interactive and cause students' interest in learning to decrease. The purpose of the research was to analyze the use of Augmented Reality (AR)-based Assemblr Edu media in increasing the learning interest of students in class X of Computer and Network Engineering at SMK Unitomo Surabaya. The study used a descriptive qualitative approach of 33 students. Data was collected through observation, interviews, documentation, and learning outcome tests. Research shows that the implementation of Assemblr Edu significantly increases students' interest in learning, characterized by enthusiasm, activeness of questioning, independent exploration, and collaboration. Cognitive learning outcomes also improved with an average post-test score of 83.2-84.3 and a completeness of 83.6%, compared to a pre-test of 75.6-76.2 with a completeness of 75.9%. An effective Edu assembly creates immersive and interactive learning, thereby increasing students' interest and learning outcomes. Teachers need to be able to consider the integration of AR technology and training.